Variação de carboidratos em folhas da videira 'Itália' submetida a diferentes de níveis de desfolhas - Souza, Essione R. [UNESP]; Ribeiro, Valtemir G.; Dantas, Bárbara F.; Filho, José M.P. Lima (Revista Brasileira de Ciencias Agrarias, 2013)
The objective of this study was to evaluate the variation of carbohydrates, proteins and free amino acids in vine leaves in cv. Italy under different levels in different phases phenological defoliation. The experimental design was randomized blocks in factorial scheme 4 (5, 10, 15 and 20 sheets left in the industry) X 4 (phenological phases at 60, 72, 84 and 106 days after pruning) and three replications. We selected leaves were exposed to sunlight, fully extended, opposite the bunch, with no signs of senescence and healthy for the indirect measurement of chlorophyll (chlorophyll index) in SPAD readings using portable chlorophyll meter SPAD-502. The leaves were subjected to quantitative analysis of proteins, amino acids, starch, total sugars, reducing sugars and sucrose. The starch content was high in the initial softening of berries and sheets 15 left on the field of production and low at the start of the ripening of fruits. 15 The amount of leaves left on the branches of production in grapevine cv. Italy is recommended, therefore, these plants showed greater efficiency in both transmission and reserve accumulation and this accumulation was influenced by the phenological stage of grapevine.
Variation of carbohydrates in leaves of Italia grapevine under different levels of defoliation
Keywords: Macromolecules; Number of leaves; Vitis vinífera L.